IBM Cloud private application developer's guide - Azraq, Ahmed (IBM redbooks., 2019)
IBM® Cloud Private is an application platform for developing and managing containerized applications across hybrid cloud environments, on-premises and public clouds. It is an integrated environment for managing containers that includes the container orchestrator Kubernetes, a private image registry, a management console, and monitoring frameworks. This IBM Redbooks® publication covers tasks that are performed by IBM Cloud"!Private application developers, such as deploying applications, application packaging with helm, application automation with DevOps, using Microclimate, and managing your service mesh with Istio. The authors team has many years of experience in implementing IBM Cloud Private and other cloud solutions in production environments. Throughout this book, we used the approach of providing you the recommended practices in those areas. As part of this project, we also developed several code examples, which can be downloaded from the Redbooks GitHub web page. If you are an IBM Cloud Private application developer, this book is for you. If you are an IBM Cloud Private systems administrator, you can see the IBM Redbooks publication IBM Private Cloud Systems Administrator's Guide, SG248440